Influence of the Ecological System of Illyricum on the Process of Croatian Ethnogenesis (Archaeologia Adriatica, 2009)
The author tries to explain how the eco system of Illyricum affected newly arrived Croats in the Migration Period. He emphasizes that the aim of conquerors was to win natural resources of Illyricum (primarily cattle raising routes) and to connect regions. In the process of integration with indigenous population Croats accepted many of their cultural traits, but also characteristics of their mentality. In the atmosphere of constant threats throughout history, even prior to the arrival of Croats, in mountainous regions, an agressive "Dinaric" component developed which is a general human characteristic and it cannot be attributed solely to the "Dinarians" who despite this characteristic have always exhibited intellectual and creative abilities. Sociogeographic conditions and threats from the "others" in these regions influenced creation of particular ideology accepted by newly arrived Croats. This ideology, as the author stresses, found its expression in epic poetry which probably has its roots in Illyrian creativity. Ecosystem of Illyricum influenced formation of agrarian/cattle-raising communities which regulated social relations and the relation of community members towards nature by customary law. This relation was defined in the statutes of coastal communes and in the laws of the northern Croatian littoral and islands. In order to maintain stability of the ecosystem of Illyricum, way of life almost did not change until "modernization shock" and "ecological revolution" (nature destruction). In the region of old Illyricum these phenomena appeared late in comparison with the European development, but in the 19th, and particularly 20th century, they caused difficult traumas in patriarchal population. The author concludes that historiography which does not take into consideration ancient culturological and genetical inheritance and awakening of archetypes in terms of transgenerational transitions will never be able to interpret the tragedy of the peoples from the Mediterranean-Danubian region. We need to learn about the Kraljević Marko syndrome and to supress it in order to use creative potentials of the patriarchal population.
Keywords: ecohistory; the Slavs; the Croats; the Dalmats; Mediterranean-Danubian region; natural resources; cattle breeding; transgenerational transitions of emotions; archetypes; Kraljević Marko syndrome; epics